Lycopene increases metabolic activity of rat liver CYP2B, CYP2D and CYP3A - Nosková, Kristýna; Dovrtělová, Gabriela; Zendulka, Ondřej; Strakošová, Markéta; Peš, Ondřej; Juřica, Jan (Pharmacological reports, 2020)
BACKGROUND: Lycopene as a naturally occurring carotenoid is a common part of the human diet. Several beneficial properties of lycopene have been identified, with the most studied being anti-cancer and antioxidant activity. However, no evidence of possible drug-drug or drug-food supplement interactions has been found. METHODS: We studied the in vivo effect of lycopene on the selected rat liver cytochromes P450 (CYPs): CYP1A2, CYP2B, CYP2C11, CYP2C6, CYP2D, and CYP3A. Lycopene was administered to rats intragastrically at doses of 4, 20, and 100 mg/kg/day for 10 consecutive days. Total protein content, P450 Content, and metabolic activity of selected CYPs were evaluated in the rat liver microsomal fraction. RESULTS: Increased CYP2B, CYP2D, and CYP3A metabolic activities were observed in animals treated with the lycopene dose of 100 mg/kg/day. The content of CYP3A1 protein was increased by the dose of 100 mg/kg/day and CYP3A2 protein was increased by all administered doses of lycopene. CONCLUSION: The results of our study indicate that lycopene increased the metabolic activity of enzymes that are orthologues to the most clinically important human enzymes involved in xenobiotic metabolism. The risk of pharmacokinetic interactions between lycopene dietary supplements and co-administered drugs should be evaluated.
Keywords: jaterní mikrozomy; Microsomes, Liver; lykopen; Dose-Response Relationship, Drug; CYP3A; Cytochrome P450; Rat; Lycopene; krysa rodu Rattus; Antioxidants; zvířata; potkani Wistar; antioxidancia; Cytochrome P-450 Enzyme System; Rats, Wistar; Male; Rats; vztah mezi dávkou a účinkem léčiva; Animals; Induction; mužské pohlaví; systém (enzymů) cytochromů P-450